High-intensity events in international women`s team handball matches - Luteberget, L. S.; Spencer, M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: International women`s team handball is a physically demanding sport and is intermittent in nature. The aim of the study was to profile high-intensity events (HIEs) in international women`s team handball matches with regard to playing positions.